Ecosystem Monitoring: Collective Species and Environmental Information - Convertino, Matteo; Li, Jie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Ecological patterns are the manifestation of salient feedback between species and the environment, considering both the natural and built environment. Mapping this dynamical feedback over space and time means extracting the structural and functional networks of habitats and species whose nexus defines the systemic function that can be preserved and enhanced via protection and eco-engineering solutions. The key is to sense the ecological collective behavior that is salient for quantitative ecosystem assessment, forecasting, and engineering. This Topic aims to highlight data, methods, inferred processes, and solutions about collective ecological patterns at multiple scales and for diverse ecosystems. The core objective is to stress the crucial importance of ecological information and monitoring for detailed and quantitative assessment of ecosystems on which future nature-based solutions can be developed considering climate risks and population values.